Solitary Radiopacity Associated with Root of Unerupted Supernumerary Tooth - A Case Report and Differential Diagnosis - Chinmaya G J; Poornima R; Sujatha G P; Ashok L (Rajiv Gandhi University of Health Sciences, 2024)
Radiopaque lesions of jaws are innumerable and variable in appearance. There are several radiopaque lesions seen in the periapical region of tooth root which are indistinguishable from other lesions. The diagnosis and management of these lesions from clinical and radiographic features could be challenging to the dentist. Alterations in the bone could be inflammatory cystic odontogenic and non-odontogenic neoplastic reactive vascular traumatic dysplastic or metabolic in origin. As intraoral periapical radiographs IOPA provide the best image resolution they can aid in identifying the subtle changes in the bone architecture periodontal ligament Pdl space and lamina dura. Radiographic analysis of the involvement of adjacent structures using panoramic imaging is not sufficient for diagnosis as it provides 2D imaging of a 3D object. Cone Beam Computed Tomography CBCT provides an accurate 3D image of the involvement of bone and adjacent structures. Systematic radiologic analysis of lesions based on their location size shape borders internal structure effect on surrounding structures and consideration of clinical signs and symptoms enable clinicians to arrive at a reliable diagnosis. Here we present a case report of an asymptomatic radiopaque lesion associated with the root of an unerupted supernumerary tooth which was accidentally detected on an IOPA taken for treating the adjacent tooth.